Estimation of the soil-water characteristic curve in sandy soils using the filter paper test - Lizana Olarte, Diego Edson Meliton (2023)
The mechanics of unsatured soils are strongly related to the suction phenomenon that occurs between solid soil particles, which change when the water content of the soil does not remain constant. The soil-water characteristic curve (SWCC) provides information related to soil suction and water content; and to obtain said curve, different direct and indirect methods can be used. In this research, the soil-water characteristic curve for sand is obtained by implementing the filter paper test. For this, three reconstituted samples of sandy soils from Lima - Peru (relative density between 20% and 60%) were tested following the wet trajectory of the curve. Samples were stored for at least seven days until equilibrium was reached. In tihs way, discrete points of the soil-water characteristic curve were obtained. SWCC equations such as Brooks and Corey (1964), Van Genuchten (1980) and Frendlund and Xing (1994) were used to fit the data and obtain their respective parameters for sandy soils. The results show that the filter paper test can be used to obtain the soil-water characteristic curves of reconstituted sandy soils; and that matric suction of sandy soil can be obtained within a period of seven days by this method; while longer storage time might be required to reach equilibrium and obtain full suction for these soils